2001
DOI: 10.1007/s004210100402
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of skeletal myosin in endurance-trained rats (I). A quantitative study

Abstract: The aim of this study was to quantify modifications in the expression of skeletal myosin light chain (MLC) and myosin heavy chain (MHC) isoforms of five muscles, according to their fiber composition and function, following endurance training in rats. Rodents were assigned randomly to one of two groups: caged sedentary controls (C) or endurance-trained rats (T). In T rats, three out of the four fast and mixed muscles studied exhibited a significant increase in the expression of MLC1s, 1f and 2s and a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Wahrmann, Winand and Rieu [27] quantified changes in MyLC isoforms in different muscles during exercise. They claim that, in order to better understand the function of MyLC in skeletal muscle it is necessary to study changes in MyLC in parallel with the quantification of MyHC under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wahrmann, Winand and Rieu [27] quantified changes in MyLC isoforms in different muscles during exercise. They claim that, in order to better understand the function of MyLC in skeletal muscle it is necessary to study changes in MyLC in parallel with the quantification of MyHC under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Most exercise studies focus on the assessment of the composition of MyHC, because of its regulatory role in myosin ATPase activity and therefore in the velocity of muscle fiber shortening [5,9]. Only in a few studies has attention been paid to the simultaneous effect of exercise on the composition of MyHC and MyLC isoforms [23,27]. It is particularly unclear how exercise of different intensity and duration affects the changes in the relative content of MyLC isoforms and their distribution in different muscles.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of endurance training on muscle MHC isoforms are well established. Many investigations (6,15,17,20,25,37,38,39) have demonstrated that this type of muscular activity promotes significant transformation of fast-to-slow MHC isoforms within both slow and fast skeletal muscles. Such shift in the total muscle MHC pool is not due to selective changes in fiber size but is due to a training-induced transformation in MHC isoforms expressed by individual fibers.…”
Section: Discussionmentioning
confidence: 99%
“…CB administration or HU. These two models were chosen for several reasons: (i) they permitted us to achieve a large range of slow-to-fast muscular modifications with the appearance of a large diversity of transformed fibres, (ii) insofar as the studies on MHC and MLC isoforms in transformed fibres have been based essentially on increased neuromuscular activity experiments, for instance chronic, low-frequency stimulation [1,13,20] or endurance training [29], these models will add to our understanding of the concept of muscle plasticity all over the (slow↔fast) spectrum of fibre types and (iii) they will allow us to determine whether, according to our previous studies on MHC and MLC isoforms at the whole muscle level, differences exist at the single fibre level between the adaptive responses of soleus muscle. The slow postural soleus muscle was particularly affected by these two conditions, other hindlimb muscles being less modified (extensor digitorum longus<red gastrocnemius<soleus) [25].…”
Section: Introductionmentioning
confidence: 99%